Insects as protein supplements for livestock production: a sustainable and efficient alternative - Montero-Prado, Pablo; Montero Atencio, Rolando; Atencio-Valdespino, Randy (Agronomía Mesoamericana, 2024)
Introduction. The agricultural sector faces the challenge of finding sustainable alternatives for animal feed, given the growing demand for food and environmental problems. Objective. To document the outstanding nutritional characteristics of insects and their potential as a food alternative for livestock production. Methodology. A bibliographic search was conducted in the Science Direct database, based on terms related to the consumption and production of animal feed and its environmental impact. Development. The nutritional profile of insects is remarkable due to their content of proteins (32 to 74 %), essential amino acids (8 to 39 %), healthy fats (6 to 21 %), and vitamins and minerals (up to 278.3 mg per 100 g of dry matter). The high digestibility of their nutrients makes them an important option to complement the animal diet. However, their use carries risks such as allergies, contamination, and nutritional imbalances, which can be minimized with proper hygiene practices, ensuring the quality of insects used, and complying with relevant regulations. Conclusions. Insects are an important source of proteins, amino acids, fats, and minerals, with quality comparable to other traditional sources such as soybeans, wheat, improved grasses, and other legumes. The use of insects represents an innovative and sustainable alternative for animal diet, as it provides a balanced and nutritious food source, benefiting both animals and the environment. Successful adoption requires a balance between nutritional and environmental advantages and the costs associated with production and regulation.